2010
DOI: 10.2478/10004-1254-61-2010-2049
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Biogenic Amines and Endotoxin in Squid, Musky Octopus, Norway Lobster, and Mussel Stored at Room Temperature

Abstract: Little research has been published on the indicators of spoilage in Mediterranean molluscan shellfi sh and crustaceans. Thus is why we studied changes in the concentrations of endotoxin and four biogenic amines (histamine, putrescine, tyramine and cadaverine) in European common squid (Loligo subulata, Lamarck, 1798), musky octopus (Eledone moschata, Lamarck, 1798), Norway lobster (Nephrops norvegicus, Linnaeus, 1758), and mussel (Mytilus galloprovincialis, Lamarck, 1819) from the Adriatic Sea stored at room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…Hal ini sesuai dengan standar (BSN, 2006), batas maksimum TPC untuk ikan segar adalah 5.0x10 5 CFU/g. Akan tetapi, hasil penelitian Prester et al (2010) menyimpulkan bahwa karakteristik secara mikrobiologis yang baik belum tentu menunjukkan kondisi bahan baku baik, karena indeks amin biogenik (histamin, putressin, tyramin, dan kadaverin) mempunyai korelasi yang tinggi terhadap kandungan endotoksin dari cumi-cumi (r=0.978 dengan p<0.001) dan musky octopus (r=0.874 dengan p<0.01), bahkan kandungan endotoksin yang tinggi berkorelasi dengan dekomposisi bahan dan peningkatan kandungan histamin. Hal ini yang perlu diwaspadai pada pengolahan bahan pangan, khususnya hasil perikanan.…”
Section: Hasil Dan Pembahasan Karakteristik Jeroan Ikan Cakalang Sebaunclassified
“…Hal ini sesuai dengan standar (BSN, 2006), batas maksimum TPC untuk ikan segar adalah 5.0x10 5 CFU/g. Akan tetapi, hasil penelitian Prester et al (2010) menyimpulkan bahwa karakteristik secara mikrobiologis yang baik belum tentu menunjukkan kondisi bahan baku baik, karena indeks amin biogenik (histamin, putressin, tyramin, dan kadaverin) mempunyai korelasi yang tinggi terhadap kandungan endotoksin dari cumi-cumi (r=0.978 dengan p<0.001) dan musky octopus (r=0.874 dengan p<0.01), bahkan kandungan endotoksin yang tinggi berkorelasi dengan dekomposisi bahan dan peningkatan kandungan histamin. Hal ini yang perlu diwaspadai pada pengolahan bahan pangan, khususnya hasil perikanan.…”
Section: Hasil Dan Pembahasan Karakteristik Jeroan Ikan Cakalang Sebaunclassified
“…Therefore, their accumulation in a variety of products such as Indian mackerel (Rastrelliger kanagurta), barramundi (Lates calcarifer), mackerel (Pneumatophorus japonicus), carp (Cyprinus carpio), orange-spotted grouper (Epinephelus coioides), hake (Merluccius merluccius), tigertoothed croaker (Otalithes ruber), milk Fish (Chanos chanos), and Indian whiting (Sillago indica) has been studied (Arulkumar, Karthik, Paramasivam, & Rabie, 2017;Bakar, Yassoralipour, Abubakar, & Rahman, 2010;Bita, Malekpouri, Mohammadian, Varzi, & Kochaian, 2015;Jiang et al, 2013;Chong, Abubakar, Rahman, Bakar, & Zaman, 2014;Krizek, Vacha, Vorlova, Lukasova, & Cupakova, 2004;Moini et al, 2012;Ruiz-Capillas & Moral, 2001). Regarding crustaceans, the biogenic amine content of humpback shrimp (Pandalus hypsinotus) and swimming crab (Portunus trituberculatus) available in retail markets of Korea (Kim, Mah, & Hwang, 2009) as well as their accumulation during storage of shrimp species (Litopenaeus setiferus, L. brasiliensis, and L. vannamei) and Norway lobster (Nephrops norvegicus) have been reported (Benner, Staruszkiewicz, Rogers, & Otwell, 2003;Prester, Orct, Macan, Vukusic, & Kipcic, 2010). In addition, the composition of the microecosystem that develops during storage of Norway lobster tail meat has been assessed (Bekaert, Devriese, Maes, & Robbens, 2015;Gornik, Albalat, Macpherson, Birkbeck, & Neil, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…reported the accumulation of putrescine and cadaverine during storage of L. setiferus at 0 and 12 C for 16 and 4 days, respectively, as well as L. brasiliensis at 24 and 36 C for 48 and 24 hr, respectively. Finally,Prester et al (2010) reported the increase of putrescine content during storage of Norway lobster at 22 C for 24 hr. Interestingly, in the latter study, histamine, tyramine, and cadaverine were not detected during storage Bita et al (2015).…”
mentioning
confidence: 98%
“…In the case of storage of crustaceans, which are histidine rich, the deteriorative process is often associated with histamine formation . Hygienic qualities, handling and storage (time and temperature) are factors determining the level of histamine in seafood . Histamine in fresh seafood stored for 12 h at room temperature reached >75 µg g −1 (wet weight) and accumulate to over 500 µg g −1 (wet weight) in commercial canned seafood .…”
Section: Introductionmentioning
confidence: 99%
“…Hygienic qualities, handling and storage (time and temperature) are factors determining the level of histamine in seafood . Histamine in fresh seafood stored for 12 h at room temperature reached >75 µg g −1 (wet weight) and accumulate to over 500 µg g −1 (wet weight) in commercial canned seafood . Several bacteria possess histidine decarboxylase, an enzyme which transforms the free amino acid histidine into histamine .…”
Section: Introductionmentioning
confidence: 99%